Assessment of Traditional Rainwater Harvesting System in Barren Lands of a Semi-Arid Region - Parker, Alison (Cranfield University, 2021)
Field and modelling data
Keywords: water harvesting'; 'aquifer recharge'; 'Hydrogeology'